Komunikasi Pemasaran Digital Produk Skincare Scarlett Whitening dengan Brand Ambassador EXO - Safrina Suryaningsih; Ayu Ningtias (UNISBA Press, 2023)
Abstract. Digital marketing communication has become an important aspect in the skincare industry, especially in the ever-evolving digital era. This abstract presents an analysis of the use of digital marketing communication strategies of Scarlett Whitening products in the promotion and increase in sales of skincare products. This study identifies and evaluates the various digital marketing communication methods and tools used by Scarlett Whitening skincare company in facing challenges and capitalizing on opportunities in a competitive market. The study involves data collection from primary and secondary sources, including literature reviews and industry reports. The results show that Scarlett Whitening's effective digital marketing communication strategies include the use of social media, content marketing, influencer marketing, search engine optimization, and online purchasing strategies. Abstrak. Komunikasi pemasaran digital telah menjadi aspek penting dalam industri produk perawatan kulit, terutama dalam era digital yang terus berkembang. Abstrak ini menyajikan analisis mengenai penggunaan strategi komunikasi pemasaran digital produk Scarlett Whitening dalam promosi dan peningkatan penjualan produk skincare. Penelitian ini mengidentifikasi dan mengevaluasi berbagai metode dan alat komunikasi pemasaran digital yang digunakan oleh perusahaan skincare Scarlett Whitening dalam menghadapi tantangan dan memanfaatkan peluang di pasar yang kompetitif. Studi ini melibatkan pengumpulan data dari sumber-sumber primer dan sekunder, termasuk tinjauan literatur dan laporan industri. Hasil penelitian menunjukkan bahwa strategi komunikasi pemasaran digital Scarlett Whitening yang efektif mencakup penggunaan media sosial, konten pemasaran, influencer marketing, optimisasi mesin pencari, dan strategi pembelian online.